Effectiveness of The Fish Diversity in Kampar Regency Book to Promote Creative Thinking of High School Students - Firman Syah; Yustina Yustina (Universitas Sebelas Maret, 2020)
The diversity of fish in Kampar regency is quite high and it can be used as information for World education, especially for teachers and students in the school, thus the book of fish diversity in Kampar was developed. This research aimed to analyze the effectiveness of the fish diversity book to see the creative thinking skills. This quasi-experimental study used a pretest-posttest control group design. The independent variable was learning using the book Fish Diversity in Kampar, and the dependent variable was the students’ creative thinking ability. Data were collected using a multiple-choice test with four creative thinking indicators: fluent, flexible, original, and detailed thinking. Hypothesis analysis used an Independent t-test. The result showed that the experiment class performed better than the control class in all indicators. Fluent thinking was 66 (adequate) for control, and 88 for an experimental class or very good; flexible thinking was 74 for control and 88 for the experiment; original thinking in the control class was 74 and scored 93 for the experimental group; detailed thinking in the control class was 71 and scored 91 in the experimental group. The hypothesis test showed that t-count> t-table with a value of -12.883> 2.002. In conclusion, the Book Fish Diversity Kampar Regency effectively improved the creative thinking of students on the topic of biodiversity